Pityriasis rosea manifesting only with a herald patch - Drago, Francesco; Varesano, Serena; Herzum, Astrid; Ciccarese, Giulia (Dermatology Reports, 2025)
Dear Editor,Pityriasis rosea (PR) is an acute, self-limited exanthematous disease associated with the endogenous systemic reactivation of human herpesvirus (HHV)-6 and/or HHV-7. The disease typically begins with a single erythematous plaque called the “herald patch” (HP), followed by a secondary generalized, symmetrical eruption. Rarely, PR can be limited only to the herald patch. The clinical and laboratory features of these atypical PR have been poorly investigated. [...]